Manajemen Pembiayaan Pendidikan Di Sekolah - Nurhakim, Haditsa Qur'ani (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
Financing Management is a process in optimizing existing funding sources, allocating available funds and distributing them as facilities or means of supporting the learning process so as to create an effective and efficient learning process. Education financing is an instrumental input component that is very important in preparing human resources through the implementation of education in schools. There is almost no educational effort that can be influenced by costs, so without the education process it will not work. The financial management process in schools includes: Budget planning, Strategy for finding sources of school funding, Use of school finances, Budget monitoring and evaluation and Accountability. School financial sources are: Financial sources and school financing are grouped into three, namely (1) Central and regional governments intended for educational purposes (2) Parents or students (3) Society.